2023
DOI: 10.5267/j.ijdns.2022.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of e-WOM on customer satisfaction through ease of use, perceived usefulness and e-wallet payment

Abstract: Currently, streaming applications have been widely used by users to get comfort and pleasure in life. Users communicate with each other on social media related to the activities carried out. Communication is formed online as electronic word of mouth (e-WOM) between one user to another. The data distributed was 1238 respondents using streaming applications and 324 respondents in Indonesia who had used e-wallet payments as members. The analysis data was to answer all research hypotheses using partial least squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…With the development of technology, individuals can shop using credit services such as credit cards and the PayLater application (Felipe et al, 2023;Modesto Veludo-de-Oliveira et al, 2014). Individuals are not burdened with owning money in digital wallets because payments will be suspended at the end of the period, leading to overspending (Nugroho et al, 2023). This is because individuals often need to think about consumer goods and have the assumption that they can repay in the future.…”
Section: Excessive Use Of Sns With Credit Overuse Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of technology, individuals can shop using credit services such as credit cards and the PayLater application (Felipe et al, 2023;Modesto Veludo-de-Oliveira et al, 2014). Individuals are not burdened with owning money in digital wallets because payments will be suspended at the end of the period, leading to overspending (Nugroho et al, 2023). This is because individuals often need to think about consumer goods and have the assumption that they can repay in the future.…”
Section: Excessive Use Of Sns With Credit Overuse Behaviormentioning
confidence: 99%
“…On the other hand, the application PayLater often provides attractive promotional programs (Aji & Adawiyah, 2022). The promotions make people more comfortable shopping using the PayLater application system (Nugroho et al, 2023). Shops using the system application PayLater will make consumers often need more self-control to shop for products that are considered attractive (Thoumrungroje, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the lower the intensity of social media marketing carried out by companies by providing easy-to-understand and interesting information about the product or service being promoted, the lower the perceived ease of use of a person for the product or service. Furthermore, studies on the quality of social media apps in Iran show social media marketing positively affects the perceived ease of use of apps (Nugroho et al, 2023).…”
Section: Theory Of Reasoned Action (Tam)mentioning
confidence: 99%
“…Furthermore, researchers have extensively expanded and customized the UTAUT in different disciplines by incorporating numerous additional constructs that align with the specific context [28], as several studies have shown that enhancing the UTAUT with extra constructs enhances its predictive ability [29]. Scholars have incorporated new constructs into traditional technology adoption models to explore the complexities of behavioral patterns among existing and potential customers [30][31][32][33][34].…”
Section: Literature Reviewmentioning
confidence: 99%